Pengaruh Etos Kerja Terhadap Kinerja Pegawai melalui Keterlibatan Kerja Sebagai Mediator: Studi pada Kantor Gubernur Provinsi Kalimantan Timur (Lembaga Pengembangan Kinerja Dosen, 2025)
Employee performance in government institutions is a crucial factor in supporting the effectiveness of public service delivery. This study is motivated by the importance of work ethic and job engagement in influencing employee performance, particularly within the Administrative Bureau of the East Kalimantan Governor’s Office. The main objective of this research is to analyze the impact of work ethic on employee performance and to examine the mediating role of job engagement in this relationship. A quantitative method was employed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The sample consisted of all 69 employees in the bureau, selected through a saturated sampling method. The analysis revealed that work ethic has a positive and significant effect on employee performance and also significantly influences job engagement. However, job engagement was not found to significantly affect performance and did not mediate the relationship between work ethic and employee performance. The findings imply that enhancing work ethic has a more direct impact on improving employee performance than efforts focused solely on increasing job engagement. Therefore, managerial strategies should prioritize fostering a work culture grounded in ethical values, responsibility, and dedication